2015
DOI: 10.5897/ajar2014.9267
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of intensity of market participation among banana traders in western Kenya

Abstract: Traders both wholesaler and retailers play a significant role in banana markets. In Kenya the banana market is not fully developed. This demands targeted studies to assess their performance. This study aims at examining banana traders' intensity of participation in the markets and constraining factors. A survey was conducted in 2013 in four counties. One hundred and ninety traders were randomly selected using multi-stage sampling technique. Data were collected on personal, market parameters, and institutional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…This is caused by the low volumes being sold by farmers. This is in line with findings by Nalunga et al (2015), Warsanga and Kilimanjaro (2014) and Komarek (2010) who found that in East African matooke value chains, the production node is the "least profitable". However, our data cannot offer a complete picture of profitability.…”
Section: Profit Margins and Market Powersupporting
confidence: 91%
“…This is caused by the low volumes being sold by farmers. This is in line with findings by Nalunga et al (2015), Warsanga and Kilimanjaro (2014) and Komarek (2010) who found that in East African matooke value chains, the production node is the "least profitable". However, our data cannot offer a complete picture of profitability.…”
Section: Profit Margins and Market Powersupporting
confidence: 91%
“…However, Heckman selection and double hurdle models have advantage over the Tobit model. The two-step models relax the Tobit model's assumptions that: a given set of independent variables produce the same effect on the probability of participating in agricultural commercialization as well as the intensity of participation (Wooldridge, 2010), Also, Tobit model assumes that non-participation in agricultural commercialization and invariably zero traded volumes are borne out of rational choice of the individual which Komarek (2010) ascribed to probable market entry barrier. Again, Tobit model is weak as its estimation is based on the condition that the dependent variable meets a certain cut-off point, this could interfere with the true estimates of the intercept and the slope.…”
Section: Methodsmentioning
confidence: 99%